STABLE ISOTOPE AND RARE EARTH ELEMENT EVIDENCE FOR RECENT IRONSTONE PODS WITHIN THE ARCHEAN BARBERTON GREENSTONE BELT, SOUTH AFRICA - Hren M.T.; Lowe D.R.; Tice M.M.; Byerly G.; Chamberlain C.P. (My University, 2006)
There is considerable debate about the mode and age of formation of large (up to ?200 m long) hematite and goethite ironstone bodies within the 3.2 to 3.5 Ga Barberton greenstone belt. We examined oxygen and hydrogen isotopes and Rare Earth Element (REE) concentrations of goethite and hematite components of the ironstones to determine whether these deposits reflect formation from sea-floor vents in the Archean ocean or from recent surface and shallow subsurface spring systems. Goethite ?18O values range from -0.7 to +1.0? and ?D from -125 to -146?, which is consistent with formation from modern meteoric waters at 20 to 25 °C. Hematite ?18O values range from -0.7 to -2.0?, which is consistent with formation at low to moderate temperatures (40-55 °C) from modern meteoric water. REE in the goethite and hematite are derived from the weathering of local sideritic ironstones, silicified ultramafic rocks, sideritic black cherts, and local felsic volcanic rocks, falling along a mixing line between the Eu/Eu* and shale-normalized HREEAvg/LREEAvg values for the associated silicified ultramafic rocks and felsic volcanic rocks. Contrasting positive Ce/Ce* of 1.3 to 3.5 in hematite and negative Ce/Ce* of 0.2 to 0.9 in goethite provides evidence of oxidative scavenging of Ce on hematite surfaces during mineral precipitation. These isotopic and REE data, taken together, suggest that hematite and goethite ironstone pods formed from relatively recent meteoric waters in shallow springs and/or subsurface warm springs. ? 2005 Elsevier Inc. All rights reserved.
Keywords: GOETHITE; HEMATITE; IRONSTONE; RARE EARTH ELEMENT; STABLE ISOTOPE; Докембрий::Архей; Precambrian::Archean